Body / Antibody - Lawrence R. Schehr (Studies in 20th & 21st Century Literature, 1996)
Unique object in the exchange-system, the gay body occupies a locus where a phantom identity and an imagined reciprocity define the poles of the subject-object relation. Made of the right stuff, it is an object circulating in a system that tends to reproduce the concept of identity in its search for mirror images of itself. Often rejected by the world, it has recently become a cynosure equated with sickness, pestilence, and death in the age of AIDS. The representations of that object change: no longer perceived as a part of libidinal economy, it has become a mass of symptoms, having changed from being an index of sexuality into being the visible dissipation of the flesh. The gay body in the age of AIDS is the mark of a pariah with the abject nature of the outcast. The body with AIDS takes the form of a text made of many signs and with many ways of reading the checkerboard pattern of the flesh. And the AIDS-narrative turns the body into the limit of the representable.
Keywords: gay body; locus; phantom identity; identity; occupy; occupies; imagined reciprocity; poles; subject-object; relation; object circulating; mirror image; self; sickness; pestilence; death; AIDS; representation; libidinal economy; symptoms; sexuality; pariah; outcast; signs; AIDS-narrative; limit; representable; homosexual body; homosexuality; gay